Optimization of eco-waste synthesis in zinc oxidegraphene oxide for cephalexin antibiotics removal - Heshammuddin, N A; M Zailan, M T; Mohamed, R M S R; Mohd-Kamil, N A F (2023)
Cephalexin (CFX) is an antibiotic prescribed for a wide variety of conditions, including bacterial infections and urinary tract infections. It has recently been labelled as an emerging pollutant due to the high concentrations of CFX that indicate a potential risk to the environment. This research set out to discover the best conditions for producing a leachate from waste materials utilising the Eco-Zinc Oxide-Graphene Oxide (Eco-ZnO/GO) catalyst for the efficient removal of CFX. The Eco-ZnO/GO nanocomposite that were generated from waste is used for adsorption in an aqueous solution. Field Emission Scanning Electron Microscope (FESEM) was used to characterise Eco-Zno/GO nanocomposite while Response Surface Methodology (RSM) were used to optimise the removal efficiency of CFX across three factors: starting concentration, mixing speed, and contact time. Average nanoparticle sizes for Eco-ZnO and GO were measured to be 23 and 122 nm, respectively. Eco-ZnO/GO has a maximum removal efficiency of 89.55% at the optimal factor of 1000 rpm in 30 minutes when working with a concentration of 100 mg/l of CFX. The results of the study demonstrated that the waste nanocomposite technology is used to remove the material effectively, which can add to our growing body of knowledge in this area